From Brooklyn to Kuwait: Female Identity and Ethics of Care in Contemporary Fiction - Alghoraibi, Rana; Alhamad, Anoud (International Journal of Language and Literary Studies, 2026)
This paper conducts a comparative analysis of two female protagonists from The Book of V. by Anna Solomon and The Pact We Made by Layla AlAmmar through the application of Carol Gilligan’s Care Ethics theory. Grounded in feminist moral philosophy, Care Ethics emphasizes empathy, responsibility, and interpersonal relationships. The study examines how American individualism and Arab collectivism shape women’s social roles, autonomy, and identity across distinct cultural contexts. Employing a qualitative textual analysis informed by Care-focused Feminist theories, the study investigates the influence of care, pain, and gender roles on the moral development of female characters. The analysis reveals several cultural disparities, including variations in religious influence, family structure, and social mobility. Nevertheless, the findings indicate that both protagonists grapple with fundamental ethical and emotional challenges, particularly tensions between personal freedom and social obligation and the responsibilities associated with caregiving. These findings demonstrate that literature transcends cultural boundaries to address universal ethical dilemmas. They also offer a multinational perspective on identity, duty, and resistance within the framework of Care Ethics.